House feeding pattern increased male yak fertility by improving gut microbiota and serum metabolites - Zhu, Yanbin; Li, Xin; Lousang-zhaxi,; Suolang-zhaxi,; Suolang,; Ciyang,; Sun, Guangming; Cidan-yangji,; Basang-wangdui, (Frontiers in Veterinary Science, 2022)
Yaks live in an extremely harsh natural environment resulting in low reproductive performance, so yak production cannot meet local demand. In order to solve this problem, the experiment aims to explore the effect of different feeding modes on the semen quality of male yak, so as to provide a theoretical basis for improving the yield of yak in Tibet. We used the combined analysis of metabolomics and microbial sequencing to explore the underlying mechanisms that affect the difference in semen quality between the house feeding (HF) group and the free range (FR) group. The result showed that the sperm motility and sperm concentration in HF group were significantly increase than FR group, the abnormal sperm rate in HF was lower compared to FR. HF modes increased some beneficial materials in blood and testis especially some antioxidants, unsaturated fatty acid and amino acids. HF group increased some gut microbes in genus level namely Rikenellaceae, Bacteroides, Prevotellaceae_UCG-004, Bacteroidales_RF16, Alloprevotella, DgA-11; It was interesting that blood metabolites, testicular metabolites, and fecal microbiota were well correlated with sperm parameters; Meanwhile, the blood metablites and testicular metablites were well correlated with microbes. The result indicated that house feeding model was benefit to yak semen quality through improving the gut microbiota and blood/testicular metabolism to increase yak fertility.